Abundance in proteins expressed after functional electrical stimulation cycling or arm cycling ergometry training in persons with chronic spinal cord injury. (4th July 2017) - Gorgey, Ashraf S.; Graham, Zachary A.; Bauman, William A.; Cardozo, Christopher; Gater, David R.
Abstract : Study design : Longitudinal design. Objectives : The study determined the effects of two forms of exercise training on the abundance of two proteins, (glucose transporter-4 [GLUT-4], adenosine monophosphate kinase [AMPK]) involved in glucose utilization and the transcriptional coactivator that regulates the genes involved in energy metabolism and mitochondrial biogenesis (peroxisome proliferator-activated receptor (PPAR) coactivator 1 alpha [PGC-1α]), in muscles in men with chronic motor-complete spinal cord injury (SCI). Settings : Clinical trial at a Medical Center. Methods : Nine men with chronic motor-complete SCI participated in functional electrical stimulation lower extremity cycling (FES-LEC; n = 4) or arm cycling ergometer (arm-cycling ergometer [ACE]; n = 5) 5 days/week for 16 weeks. Whole body composition was measured by dual energy X-ray absorptiometry. An intravenous glucose tolerance test was performed to measure glucose effectiveness (Sg) and insulin sensitivity (Si). Muscle biopsies of the right vastus lateralis (VL) and triceps muscles were collected one week prior to and post the exercise training intervention. Results : Neither training intervention altered body composition or carbohydrate metabolism. GLUT-4 increased by 3.8 fold in the VL after FES training and increased 0.6 fold in the triceps after ACE training. PGC-1α increased by 2.3 fold in the VL after FES training and 3.8 fold in the triceps after ACE training. AMPK increased by 3.4 fold in the VL after FES training and in the triceps after ACE training. Conclusion : FES-LEC and ACE training were associated with greater protein expressions in the trained muscles by effectively influencing the abundance of GLUT-4, AMPK and PGC-1α. Thus, FES-LEC training of paralyzed muscle can modulate protein expression similar to that of trained and innervated muscle.